2021
DOI: 10.3390/cancers13112782
|View full text |Cite
|
Sign up to set email alerts
|

Early Survival Prediction Framework in CD19-Specific CAR-T Cell Immunotherapy Using a Quantitative Systems Pharmacology Model

Abstract: Chimeric antigen receptor (CAR)-T cell therapy has revolutionized treatment of relapsed/refractory non-Hodgkin lymphoma (NHL). However, since 36–60% of patients relapse, early response prediction is crucial. We present a novel population quantitative systems pharmacology model, integrating literature knowledge on physiology, immunology, and adoptive cell therapy together with 133 CAR-T cell phenotype, 1943 cytokine, and 48 metabolic tumor measurements. The model well described post-infusion concentrations of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…Prediction of the late response of patients to CAR T-cell therapy during early treatment stage will greatly improve patient outcomes by guiding the treatment regimen that follows, especially for patients with acute disease progression. [36][37][38] Having demonstrated that our computational model accurately recapitulated the cellular dynamics of CAR T-cell therapy, we found that the response can be differentiated by the actual function level and dynamics of CAR T-cells in individual patients. Thus, we hypothesized Open access that such responses can be predicted using our computational immuno-oncology model with input of clinically measurable and available patient information related to CAR T-cell dynamics, such as the peak value and AUC7 (area under the curve from days 0 to 7) of CAR T-cells, at the early stage of CAR T-cell treatment.…”
Section: In Silico Prediction Of Late Response At Early Stage Of Car ...mentioning
confidence: 79%
“…Prediction of the late response of patients to CAR T-cell therapy during early treatment stage will greatly improve patient outcomes by guiding the treatment regimen that follows, especially for patients with acute disease progression. [36][37][38] Having demonstrated that our computational model accurately recapitulated the cellular dynamics of CAR T-cell therapy, we found that the response can be differentiated by the actual function level and dynamics of CAR T-cells in individual patients. Thus, we hypothesized Open access that such responses can be predicted using our computational immuno-oncology model with input of clinically measurable and available patient information related to CAR T-cell dynamics, such as the peak value and AUC7 (area under the curve from days 0 to 7) of CAR T-cells, at the early stage of CAR T-cell treatment.…”
Section: In Silico Prediction Of Late Response At Early Stage Of Car ...mentioning
confidence: 79%
“…administration, whereas lower volumetric blood flow rate at the hepatic artery injection site near the tumor is beneficial for CAR T distribution to the hepatic tumor. As current investigation brought insights into the contribution of blood flow to CAR T distribution to solid tumors, future effort will strive to understand migration behavior of heterogenous CAR T subsets and phenotypes and the impact on its safety and efficacy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of this approach is the requirement of enormous T cell data measured by flow cytometry for each kind/ species, as well as longitudinal data of tumor dynamics to capture the antigen-dependent T cell kinetics. A recent model by Mueller-Schoell et al 35 incorporated four phenotypes, including naïve, central memory, effector memory, and terminally differentiated effector T cells and enabled both T cell-mediated tumor killing as well as tumor-dependent T cell proliferation. 35 However, due to the sparse data from only 19 patients, several parameters, including tumor growth rate, homeostatic proliferation rate constants, and death rate constants, are unidentifiable, and only two parameters were allowed to consider IIV during fitting.…”
Section: Modeling and Simulation Strategies Of Actmentioning
confidence: 99%
“…The challenge of this approach is the requirement of enormous T cell data measured by flow cytometry for each kind/species, as well as longitudinal data of tumor dynamics to capture the antigen‐dependent T cell kinetics. A recent model by Mueller‐Schoell et al 35 . incorporated four phenotypes, including naïve, central memory, effector memory, and terminally differentiated effector T cells and enabled both T cell‐mediated tumor killing as well as tumor‐dependent T cell proliferation 35 .…”
Section: Modeling and Simulation Strategies Of Actmentioning
confidence: 99%